Pengaruh Reputasi Auditor, Audit Client Tenure dan Opinion Shopping terhadap Penerimaan Opini Audit Going Concern - Al Khodiman; Erinos NR (Universitas Negeri Padang, 2023)
The study was conducted to examine the effect of auditor reputation, audit client tenure and opinion shopping on going concern audit opinion acceptance. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the 2017-2021 observation year. The sample used is 690 companies that use purposive sampling technique in selecting the use of the sample. The statistical method used is logistic regression analysis with the results obtained that the auditor's reputation has a significant negative effect on the acceptance of going concern audit opinions while audit client tenure and opinion shopping have no significant positive effect on the acceptance of going concern audit opinions in manufacturing companies in 2017-2021 observations.